Use of synchrotron radiation SAXS to study the first steps of the interaction between sodium dodecyl sulfate and charged liposomes. Issue 3 (2002) - López López, O. O.; Cócera Cócera, M. M.; Pons Pons, R. R.; Amenitsch Amenitsch, H. H.; Caelles Caelles, J. J.; Parra Parra, J. L. J. L.; Coderch Coderch, L. L.; de la Maza de la Maza, A. A.
Abstract : The technique of time resolved small angle X–ray scattering (SAXS) using a synchrotron radiation source was used to study the structural transformations as well as the kinetic associated with the first steps of the solubilization of liposomes induced by the anionic surfactant sodium dodecyl sulfate (SDS). Neutral and electrically charged (anionic and cationic) liposomes were used to investigate the effect of the electrostatic charges on these initial steps. The mechanism that induces the solubilization process consisted in an adsorption of surfactant on the bilayers and a desorption of mixed micelles from the liposomes surface to the aqueous medium. Regardless of the type of charge of the liposome the time needed for the desorption of the first mixed micelles was shorter than that for the complete adsorption of the surfactant on the liposomes surface. The present work demonstrates that the adsorption of the SDS molecules on liposomes was slower when the charges of surfactant and lipids were the same. As for the release of mixed micelles from the surface of these liposomes, this process was slower when the charges of surfactant and lipids were opposite.